Measurement of the front-end dead-time of the LHCb muon detector and evaluation of its contribution to the muon detection inefficiency. (6th April 2016) - Anderlini, L.; Anelli, M.; Archilli, F.; Auriemma, G.; Baldini, W.; Bencivenni, G.; Bizzeti, A.; Bocci, V.; Bondar, N.; Bonivento, W.; Bochin, B.; Bozzi, C.; et al.
Abstract: A method is described which allows to deduce the dead-time of the front-end electronics of the LHCb muon detector from a series of measurements performed at different luminosities at a bunch-crossing rate of 20 MHz. The measured values of the dead-time range from ∼ 70 ns to ∼ 100 ns. These results allow to estimate the performance of the muon detector at the future bunch-crossing rate of 40 MHz and at higher luminosity.